Recommendation System For Choosing The Best Laptop For Informatics Students Using The SMART Method - Depi Sihotang; Bustami; lidyarosnita (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
In the rapidly advancing digital era, the use of laptops has become an essential need, especially for students. The problem of choosing the right laptop is still often experienced by many students. This issue arises due to a lack of knowledge in selecting laptops with good specifications and affordable prices, so purchasing decisions are often based on friends' recommendations or advertisements that do not always meet their academic needs optimally. This research uses the Simple Multi Attribute Rating Technique (SMART) method. SMART is a flexible decision-making method. The process of determining the best laptop involves criteria such as price, processor type, monitor screen size, operating system, RAM, VGA type, and storage. The system provides solutions by using the SMART method to evaluate the weights and criteria that have been determined. The ranking process is carried out to determine the best laptop for students majoring in informatics. From 10 data samples for the Informatics department, the highest alternative value (A4) was obtained, namely "ACER Swift X 14 SFX14-71G-70KB" with a final score of 0.866666667, and the lowest alternative value (A8) was "ASUS VivoBook 14 A1404ZA-IPS321" with a final score of 0.166666667. The process of determining the best laptop using the Simple Multi Attribute Rating Technique (SMART) method aims to help informatics students choose laptops that suit their academic needs.